Sustainable Energy Systems in Latin America and the Caribbean Countries - Tama , Alberto; Tama , Valeria Carolina; Tama , Andrea Stephanie (Theory and Applications of Engineering Research Vol. 6, 2024)
The development of cleaner and more efficient energy technologies will play an important role in the sustainable development of a future energy strategy. The energy sources from fossil fuels represented 83.69% of the primary supply structure in 2020. The world is currently undergoing a transition with two omnipresent phenomena such as technology and climate change. The energy transition towards greater diversification and decarbonization of the global energy mix is inseparably related to international regulations on climate change and the SDGs. LAC (Latin America and the Caribbean) countries have a historical responsibility to seek support for the development of SES through the financing of energy infrastructure projects and technical assistance programs focused on its strategic guidelines. The environmental impacts associated with the production of electricity from the implementation of a certain type of energy generation technology must be evaluated and weighed, where the countries of LAC have an enormous responsibility to participate; their governments must face, through their energy systems, complicated objectives, with the purpose of ensuring energy supply to meet present and future demand, providing in turn, accessibility and affordability to energy; and promoting environmental protection and energy savings. To promote energy efficiency, not only must environmentally responsible norms or standards be established, and a regulatory framework developed, but consumer awareness and education are needed.